International migration and development in East Asia and the Pacific (The World Bank, 2014)
In this context, this study analyzes the impact of migration on development of the region and how international migration should be managed in East Asia in a way that supports development goals while simultaneously protecting the rights of migrants. The study covers: trends in international migration in East Asia and overarching regional issues such as the links between macroeconomic management and remittances and the role of demographic trends in migration; the economic impact of migration and remittances on labor-sending countries and labor-receiving countries; the migration industry; and the policies and institutions that govern migration.